THE SCHEME OF THE AUTOMATED SOLUTION OF THE PROBLEM OF OPTIMUM DISTRIBUTION OF CARGO HANDLING MECHANISMS AT THE AIRPORTS - Іваннікова, В. (Science-based technologies, 2012)
The developed with usage of the programming language C author software for solution of the problem of optimal mechanized means distribution between cargo warehouses and aircraft in airports is presented in the article.